(untitled) (Research, Society and Development, 2020)
This study examines the effects of the synthetic analog of feline pheromone (FFPA) in cats submitted to physical and ophthalmologic examination. Plasma cortisol, plasma glucose, vital parameters and blood count were evaluated for this study. Therefore, 14 felines of both sexes and clinically healthy were selected and separated into two groups: non-exposed (7), and experimental group (7). The experimental group was exposed to FELIWAY CLASSIC® diffuser associated with FELIWAY CLASSIC® spray. The animals of the exposed group remained in contact with the pheromone before and during the veterinary evaluation, totaling 3 hours and 30 minutes. After the observation period, hemogram was performed in both groups and all results were within the reference values for the species. Plasma concentrations of cortisol in the non-FFPA group ranged from 0.5 to 1.99 μg / dL, with an average of 1.3 μg / dL and in the experimental group of 0.3 to 2.88 μg / dL, with an average of 1.51 μg / dL, presenting no significant variance between groups (p>0,05). In contrast, the animals exposed to synthetic FFPA had their plasma glucose concentration and the vital parameters decreased (83.0 mg / dL and FC = 182 bpm, RR = 44.0 mpm) when compared with the animals that were not exposed (FC = 192 bpm, FR = 54.2 mpm and 87.5 mg / dL). In addition, the animals exposed to FFPA were, according to their examiners, calmer and more receptive during the procedures performed in comparison to their habitual behavior. The results of this study suggest that the use of FFPA, even in short periods, can be beneficial to cats in stressful situations, such as outpatient visits.